HOXA5 Expression Is Elevated in Breast Cancer and Is Transcriptionally Regulated by Estradiol - Hussain, Imran; Deb, Paromita; Chini, Avisankar; Obaid, Monira; Bhan, Arunoday; Ansari, Khairul I.; Mishra, Bibhu P.; Bobzean, Samara A.; Udden, S. M. Nashir; Alluri, Prasanna G.; Das, Hriday K.; Brothers, Robert Matthew; et al. (Frontiers in Genetics, 2020)
HOXA5 is a homeobox-containing gene associated with the development of the lung, gastrointestinal tract, and vertebrae. Here, we investigate potential roles and the gene regulatory mechanism in HOXA5 in breast cancer cells. Our studies demonstrate that HOXA5 expression is elevated in breast cancer tissues and in estrogen receptor (ER)-positive breast cancer cells. HOXA5 expression is critical for breast cancer cell viability. Biochemical studies show that estradiol (E2) regulates HOXA5 gene expression in cultured breast cancer cells in vitro. HOXA5 expression is also upregulated in vivo in the mammary tissues of ovariectomized female rats. E2-induced HOXA5 expression is coordinated by ERs. Knockdown of either ERα or ERβ downregulated E2-induced HOXA5 expression. Additionally, ER co-regulators, including CBP/p300 (histone acetylases) and MLL-histone methylases (MLL2, MLL3), histone acetylation-, and H3K4 trimethylation levels are enriched at the HOXA5 promoter in present E2. In summary, our studies demonstrate that HOXA5 is overexpressed in breast cancer and is transcriptionally regulated via estradiol in breast cancer cells.